Ableitungsregeln

 

Konstanten

$f\left(x\right)=c$ƒ (x)=c$f'\left(x\right)=0$ƒ '(x)=0

Potenzregel

$f\left(x\right)=x^n$ƒ (x)=xn$f'\left(x\right)=n\cdot x^{n-1}$ƒ '(x)=n·xn1

Faktorregel

$f\left(x\right)=c\cdot g\left(x\right)$ƒ (x)=c·g(x)$f'\left(x\right)=c\cdot g'\left(x\right)$ƒ '(x)=c·g'(x)

Summenregel

$f\left(x\right)=g\left(x\right)+h\left(x\right)$ƒ (x)=g(x)+h(x)$f'\left(x\right)=g'\left(x\right)+h'\left(x\right)$ƒ '(x)=g'(x)+h'(x)

Produktregel

$f\left(x\right)=u\left(x\right)\cdot v\left(x\right)$ƒ (x)=u(x)·v(x)$f'\left(x\right)=u'\left(x\right)\cdot v\left(x\right)+u\left(x\right)\cdot v'\left(x\right)$ƒ '(x)=u'(x)·v(x)+u(x)·v'(x)

Quotientenregel

$f\left(x\right)=\frac{u\left(x\right)}{v\left(x\right)}$ƒ (x)=u(x)v(x) $f'\left(x\right)=\frac{u'\left(x\right)\cdot v\left(x\right)-u\left(x\right)\cdot v'\left(x\right)}{v^2\left(x\right)}$ƒ '(x)=u'(x)·v(x)u(x)·v'(x)v2(x) 

Kettenregel

$f\left(x\right)=u\left(v\left(x\right)\right)$ƒ (x)=u(v(x))$f'\left(x\right)=u'\left(v\left(x\right)\right)\cdot v'\left(x\right)$ƒ '(x)=u'(v(x))·v'(x)

Natürliche Exponentialfunktion

$f\left(x\right)=e^x$ƒ (x)=ex$f'\left(x\right)=e^x$ƒ '(x)=ex